Testing the quiet life hypothesis in the African banking industry - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2018)
The Quiet Life Hypothesis (QLH) is the pursuit of less efficiency by firms. In this study, we assess if powerful banks in the African banking industry are increasing financial access. The QLH is therefore consistent with the pursuit of financial intermediation inefficiency by large banks. To investigate the hypothesis, we first estimate the Lerner index. Then, using Two Stage Least Squares, we assess the effect of the Lerner index on financial access proxied by loan price and loan quantity. The empirical evidence is based on a panel of 162 banks from 42 African countries for the period 2001-2011. The findings support the QLH, although quiet life is driven by the below-median Lerner index sub-sample. Policy implications are discussed.
Keywords: D40; G20; G29; L10; O55; 330; Financial access; Bank performance; Africa